Peculiarities of Singing in Chinese Popular and Traditional Music: Influence of Musical Genres on Vocals - Xia, Weitao (Música Hodie, 2023)
Under the conditions of multiculturalism, Chinese vocal art has formed its own unique theoretical system based on the characteristics of vocalization, articulation, diction, and breathing. The aims of the study are to identify singing features in Chinese popular and traditional music, as well as to determine the ways in which musical genres influence vocals. Two teachers of modern vocal, two teachers of traditional vocal, 30 students of the Vocal Arts Department of Peking University, and two art historians from the Central Conservatory of Music took part in the study. According to the study purpose, it was found that in traditional Chinese vocal arts, the main technique is falsetto (58%), mixed techniques (21.2%), vibrato (13.2%), overtone singing (6.1%), and glissando (1.5%) are also used. In popular singing the key technique is splitting (33.6%), also used: subtone (20.2%), vibrato (17.7%), drive (12.1%), glissando (11.1%), vocal fry register (9.2%), falsetto (3.3%), overtone singing (2%). As a result of the correlation analysis the dependence of popular singing techniques on traditional singing was determined. The coefficient of determination was 33.5%. It was also determined that when performing pop music, vibrato is controlled; noises and growling tones are used in rock music; uncontrolled vibrato, falsetto, and mixed techniques are used in opera; nasal sounds and minimal vibrato are in folk/country music; clear diction, articulation, slides, and scatting in blues/jazz; rhythmic and nasal sounds in hip-hop. The experiment results can be used in pedagogy for teaching vocals in China and abroad, as part of cultural activities related to the organization of events such as festivals, concerts, tourist programs, theatrical performances, etc.